Avaliação da atividade bactericida e antineoplásica de novos complexos de Ag(I) contendo semicarbazonas e trifenilfosfina como ligantes - Almeida, Vitor Yohan Grosskopf (Universidade Federal de São Carlos, 2019)
Title: EVALUATION OF BACTERIAL ACTIVITY AND ANTINEOPLASTIC OF NEW Ag(I) COMPLEXES CONTAINING SEMICARBAZONES AND TRIPHENYLPHOSPHINES AS LIGANDS. The present work aimed to evaluate the influence of ligands triphenylphosphine and semicarbazone as a biological potential as silver(I) complexes with the following formula [Ag(L)(PPh3)2]+ and [Ag(L)2]+ (L= ligands: (E)-2-((E)-3-phenylallylidene)hydrazine-1-carboxamide – CSC and (2E)-2-[(3E)-4-Phenylbut-3-en-2-ylidene]-hydrazinecarboxamide – BSC). It was synthesized and characterized 4 new silver(I) complexes: two bis(chelate) [Ag(CSC)2]NO3 = CCA and [Ag(BSC)2]NO3 = BBA; two complexes containing triphenylphosphine and CSC ligands [Ag(CSC)(PPh3)2]NO3 = (CAP) and triphenylphosphine and BSC ligands [Ag(BSC)(PPh3)2]NO3 = (BAP). The characterization of the compounds was performed using NMR 1H 13C, IR, UV-vis, molar conductivity and elemental analysis (CNH). The CHN data exhibited adequate to the proposed structure. The complexes molar conductivity showed they are cationic 1:1 and stable on dimethyl sulfoxide. On the IR spectra, it was observed displacements regarding the free ligands, watching the characteristic stretching wave numbers of C=N and C=O, which indicated donating atoms as N and O. Accomplishing cellular viability assays (MTT) against tumoral cells of breast (MDA-MB-231 and MCF7) and non-tumoral and tumoral prostate cells (PNT2 and DU-145). It was verified greater inhibitory action of the complexes containing triphenylphosphine (BAP and CAP) in comparison to the bis(chelates), and the BBA complex showed larger values of IS (IC50[PNT2]/ IC50[DU-145]) for the prostate evaluated cells (IS = 3,13). DNA interaction assays showed weak or non-interacting nature with the synthesized complexes and DNA, which suggests that the therapeutic target is another. The evaluation on bacteria inhibition evidenced that CAP complex is a promising antimicrobial agent, with a inhibitory rate higher than 70% such as Gram-positive as Gram-negative bacteria.
Evaluation of bacterial activity and antineoplastic of new Ag(I) complexes containing semicarbazones and triphenylphosphines as ligands
Keywords: Prata; Compostos de coordenação; Câncer; Bactérias; Silver; Coordination compounds; Cancer; Bacteria; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::CAMPOS DE COORDENACAO